Effects of dietary tea polyphenols on intestinal microflora and metabonomics in juvenile hybrid sturgeon (Acipenser baerii♀ × A. schrenckii ♂) - Zhao, Zhenxin; Yang, Qihui; Tan, Beiping; Lin, Huaxing; Yi, Yuanming (Aquaculture reports, 2024)
The present study aimed to evaluate the role of the modulatory effect of Tea polyphenols (TPs) on intestinal microbiota and its metabolism of juvenile hybrid sturgeon. A total of 450 fish (97.20 ± 0.18 g) were fed five diets with different concentrations of TPs mg / kg: 0 (TP-0), 100 (TP-100), 300 (TP-300), 500 (TP-500) and 1000 (TP-1000) for 56 days. The results showed that dietary 300 mg / kg TPs significantly increased villus height (VH), crypt depth (CD) and the number of goblet cells (GC) in the intestine (p < 0.05), and 1000 mg/kg TPs supplementation significantly decreased muscle thickness (MT) and villus width (VW) compared with TP-0 group (p < 0.05). With the increase of dietary TPs, relative abundance of the potential probiotics including Lactobacillus and Rhodobacteraceae were increased, while the relative abundance of potential pathogens especially Clostridiaceae were decreased. And dietary TPs at 300 mg / kg could be beneficial to its self-colonization in the intestinal microflora of sturgeon. Metabonomics analysis showed that the differential amino acids metabolites were increased and amino acids metabolism pathways were enriched with the increase of dietary TPs. The highest enriched pathways in the intestines of sturgeon were tryptophan metabolism, and protein digestion and absorption metabolism with the increase of TPs supplementation at 300 mg / kg. These results provide a novel insight into the immune-protective effect of TPs on regulating the intestinal microbiota and metabolism, which are helpful for thoroughly understanding the function of TPs and providing a solid basis for the deeper utilization of TPs as a natural feed additives. •Tea polyphenols treatment improved the intestine morphological parameters.•Tea polyphenols treatment regulated the composition and structure of gut microbiota.•The amino acids metabolism pathways were enriched with the increase of dietary tea polyphenols.